Optimal operation of flexible interconnected distribution grids based on improved virtual synchronous control techniques - Wang, Zeyi; Liu, Guangzhi; Pang, Dan; Wang, Yao; Yu, Bin; Wang, Zhenhao (Frontiers in Energy Research, 2024)
With distributed energy sources connected to the distribution grid on a large scale, for distributed photovoltaic power randomness, this paper proposes a flexible interconnection system optimization operation strategy. Firstly, the virtual synchronous control technology is improved to improve the DC bus voltage stability; secondly, it analyses the system operation mode to judge the output logic of PV and storage units, takes DC bus power balance as the underlying logic, and puts forward the power coordination optimization strategy and fault power supply restoration strategy with full consideration of factors such as the load balance degree of the distribution station area, the economic operation of the main transformer, and the amount of power lost in the faulty station area, etc. It also establishes a multiobjective optimization model to obtain the power commands of each port, and achieves the power flexibility mutualization of the flexible interconnected system through accurate regulation of the SNOP. Finally, a simulation model of the flexible interconnection system is built in Matlab/Simulink to verify the effectiveness of the proposed optimization strategy.